Impact of test protocols and material binding on the efficacy of antimicrobial wipes. Issue 1 (September 2019) - Wesgate, R.; Robertson, A.; Barrell, M.; Teska, P.; Maillard, J-Y.
Summary: Background: The use of effective cleaning/disinfectant products is important to control pathogens on healthcare surfaces. With the increasing number of wipe products available, there is a concern that combination of a formulation with the wrong material will decrease the efficacy of the product. This study aimed to use a range of efficacy test protocols to determine the efficacy of four formulations before and after binding to three commonly used wiping materials. Methods: Two quaternary ammonium (QAC)-based products, one hydrogen-peroxide-based product and one neutral cleaner were combined with microfibre, cotton or non-woven materials and tested for efficacy against Pseudomonas aeruginosa and Staphylococcus aureus with two surface tests (ASTM E2197-17 and EN13697-15) and two 'product' tests (ASTM E2967-15 and EN16615-15). Findings: Overall, the impact of using different materials on formulation efficacy was limited, except for an alkyl(C12-16 )dimethylbenzylammonium chloride-based product used at 0.5% v/v. The hydrogen peroxide product was the most efficacious regardless of the material used. The results from wipe test ASTM E2967-15 were consistent with those from the surface tests, but not with EN16615-15 which was far less stringent. Conclusions: The use of different wiping cloth materials may not impact severely on the efficacy of potent disinfectants, despite the absorption of different volumes of formulation by the materials. QAC-based formulations may be at higher risk when a low concentration is used. There were large differences in efficacy depending on the standard test performed, highlighting the need for more stringency in choosing the test to make a product claim on label.